TRENDS IN IMPROVING PROFESSIONAL TRAINING OF PHYSICAL EDUCATION SPECIALISTS IN HEI IN UKRAINE - СОГОКОНЬ, О.; ДОНЕЦЬ, О.; НОВІК, С.; ФАЗАН, В. (Педагогічні науки, 2024)
The presented article examines the trends in improving the professional training of physical culture specialists in higher education institutions in Ukraine. Academics in their practical activities must use innovative products – the latest technologies that significantly improve the quality of education, particularly in conducting distance learning courses or monitoring students’ knowledge. We believe that the use of information and communication technologies for teaching and assessing students’ knowledge creates the basis of information maintenance of the quality of education and is an important aspect of reforming the education system in Ukraine, a strategic priority area of innovative activity.